2012
DOI: 10.1364/oe.20.008192
|View full text |Cite
|
Sign up to set email alerts
|

Transmission-grating-photomasked transient spin grating and its application to measurement of electron-spin ambipolar diffusion in (110) GaAs quantum wells

Abstract: A circular dichromatic transient absorption difference spectroscopy of transmission-grating-photomasked transient spin grating is developed and formularized. It is very simple in experimental setup and operation, and has high detection sensitivity. It is applied to measure spin diffusion dynamics and excited electron density dependence of spin ambipolar diffusion coefficient in (110) GaAs quantum wells. It is found that the spin ambipolar diffusion coefficient of (110) and (001) GaAs quantum wells is close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…(By contrast, Eq. 6 shows that for n-type samples D a never decreases with n, consistent with measurements in nominally undoped 11,12 and Si-doped 15 GaAs quantum wells.) Figure 3(b) shows D a /µ h calculated for a sample doped as heavily as ours.…”
Section: Numerical Evaluation Of Eqsupporting
confidence: 77%
“…(By contrast, Eq. 6 shows that for n-type samples D a never decreases with n, consistent with measurements in nominally undoped 11,12 and Si-doped 15 GaAs quantum wells.) Figure 3(b) shows D a /µ h calculated for a sample doped as heavily as ours.…”
Section: Numerical Evaluation Of Eqsupporting
confidence: 77%
“…Spin relaxation dynamics of electrons has been studied extensively in bulk GaAs semiconductors 17 and two-dimensional GaAs quantum wells 715 . It was found that spin relaxation time of electrons was dominated by the Dyakonov-Perel (DP) spin relaxation mechanism for both (001)-oriented bulk GaAs 1, 3, 7 and two-dimensional quantum wells 10 , but the DP spin relaxation mechanism was suppressed so substantially in (110)-oriented GaAs quantum wells that spin relaxation time was prolonged significantly 14, 15 . In contrast to the extensive studies of spin relaxation of electrons, spin relaxation of holes in bulk GaAs and quantum wells was studied much less because spin relaxation of holes was much faster than one of electrons and usually hidden by spin relaxation of electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The mobility in these systems, however, is very low due to the direct doping, and they do not allow for easy manipulation of the carrier density and the Rashba spin-orbit interaction by external gate voltages. Optical measurements of spin diffusion in QWs and 2DES are in many cases more challenging, as the spin diffusion length is shorter due to fast dephasing, so that techniques such as transient spin gratings [28] or shadow gratings [29] need to be applied. Large spin diffusion lengths can be observed in (110)-grown QWs in which carrier transport is facilitated by surface acoustic waves [30][31][32] and in (110)-oriented 2DES [21,33].…”
Section: Introductionmentioning
confidence: 99%